Improvement of Spatial Learning and Memory Impairments by Fetal Neural Tissue Transplantation in Experimental Rat Model of Alzheimer’s Disease - Can, Songül Meltem; Barlas, Orhan (Bagcilar Medical Bulletin, 2019)
Objective: It is known that the acetylcholinergic afferents of the neocortex from subcortical areas participate in learning and memory. Autopsy studies in cases of Alzheimer’s disease (AD) have shown that most of the neurons of nucleus basalis magnocellularis (NBM) are atrophic or decreased in number. In this study, we searched for whether or not it was possible to improve the impaired learning and memory functions with foetal neural tissue transplantation in an experimental model of AD. Method: A total of thirty seven young adult male Wistar albino rats were served as experimental subjects. NBM on the right side was destroyed by the injection of kainic acid stereotactically so as to make a model of AD. The grafts were obtained from 14-16 day foetuses of the same genus. After the tissue with cholinergic neurons dissected from ventral forebrain and tissue with non-cholinergic neurons dissected from telencephalic vesicle, cell suspensions were prepared and injected stereotactically to the ipsilateral frontal cortex. Spatial learning and memory functions were tested by Morris’ water maze tasks. Results: Spatial learning and memory functions in rats were impaired by unilateral lesions of nucleus basalis magnocellularis. The impairment observed during the early period partially improved by the time. It was observed that this amelioration was accelerated with both cholinergic and non-cholinergic foetal neural tissue implantation. Conclusion: In our study, improvement of spatial learning and memory impairment with both cholinergic and non-cholinergic foetal neural tissue implantation can be explained by re-establishment of impaired connections via proliferation of limited number of surviving cholinergic neurons creating new synapses, as a result of upregulation of endogenous neural stem cells and activation of trophic mechanisms by implantation, rather than creation of functional synapses between the graft and the recipient tissue.